New Evidence of the Determining Factors of Medical Tourism in the United Arab Emirates - Al-Talabani, Hallow (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Medical tourism provides essential advantages for destinations. On the other hand, the knowledge of developing competitive medical tourism destinations is still limited. This study proposes a conceptual framework on novel ways of sustaining the United Arab Emirates (UAE) Vision 2020 concerning the existing models on behavior. In the current study, the Theory of Planned Behavior (TPB) is utilized along with the Finance, System, and Connection (FSC) model. The data was collected with the aid of a questionnaire. As such, the study employs finance, system, and connections variables that are commonly adopted in testing medical tourism development. The designed model incorporates three critical factors that have remained the focal points in the world of medical tourism. Hence, the results reveal the empirical evidence that the finance, system, and the connection factors significantly foster the growth of tourist arrivals in Dubai. Moreover, the medical tourism infrastructure is expected to bring significant improvement in the economy of Dubai. By employing the SMART PLS (partial least square) software package, the structural analysis model affirms the robustness of the results. Besides, the thesis presents the policy implications for the stakeholders in the health sector, the tourism sector, and the government.

ÖZ: Medikal turizm destinasyonlar için önemli avantajlar sağlar. Öte yandan, rekabetçi medikal turizm destinasyon geliştirmeye dair bilgi birikimi halen sınırlıdır. Bu çalışma, mevcut davranış modellerine atıfta bulunarak Birleşik Arap Emirlikleri (BAE) Vizyonu 2020'yi sürdürmenin yeni yolları üzerine kavramsal bir çerçeve önermektedir. Bu çalışmada, Planlı Davranış Teorisi (TPB), Finans, Sistem ve Bağlantı (FSC) modeli ile birlikte kullanılmıştır. Veriler bir anket yardımıyla toplanmıştır. Bu nedenle, araştırmada medikal turizm gelişiminin test edilmesinde sıkça benimsenen finans, sistem ve bağlantı değişkenleri kullanılmıştır. Tasarlanan model, medikal turizm dünyasında odak noktaları olmaya devam eden bu üç önemli faktörü içermektedir. Bu doğrultuda, sonuçlar finans, sistem ve bağlantı faktörlerinin Dubai'ye gelen turistlerin gelişimini önemli ölçüde artırdığına dair ampirik kanıtları ortaya koymaktadır. Ayrıca, medikal turizm altyapısının Dubai ekonomisinde önemli gelişmeler getirmesi beklenmektedir. SMART PLS (kısmi en küçük kare) yazılım paketini kullanılarak yapısal analiz modeli sonuçlarının geçerliliği onaylanmıştır. Buna ek olarak, tez sağlık sektöründeki, turizm sektöründeki ve hükümetteki paydaşlara yönelik politika tavsiyeleri sunmaktadır.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Assoc. Prof. Dr. Ali Öztüren and Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Medical Tourism--United Arab Emirates; Health and Care Tourism; Medical tourism; finance; system; connections; economic growth; diversification; UAE